Pelatihan Budidaya Maggot Black Soldier Fly sebagai Pakan Alternatif dalam Upaya Pengolahan Sampah Organik Rumah Tangga - Resti Rahayu; Eli Ratni; Henny Herwina; Robby Jannatan; Virtuous Setyaka; Wellyalina Wellyalina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The city of Padang produces approximately 600 tons of waste daily, which includes the categories of recyclable and non-recyclable waste. However, the percentage of waste that can be recycled is only about 17% and the rest must be heaped into end landfill every day. The category of recycled waste is counted as much as 65% is organic waste that is made into compost and 35% is both plastic and paper waste that is processed into other products. Maggot, which is the larva of the Black Soldier Fly, is an organic matter-decomposing agent that has better decomposition capabilities than other organisms. Maggot has biomass with high protein and fat content. Maggot farming is the most appropriate effort needed by the community today, because in addition to processing daily organic waste, it will also produce feed for livestock such as chicken, duck, fish, and bird. The farming process only requires simple technology and low cost, but is able to reduce the earth's waste load. The Andalas University community service team provided training on maggot farming to process organic waste from community households. The training was carried out using the Hybrid method, which is a combination of offline and online techniques with the same goal. The activity began with counseling on theoretical explanations, followed by both the farming practices and further program assisting. It hopes that the activity will be improved by other trainings such as Maggot’s processing into more valuable products, so that it can be packaged in such a way as to be marketed to the target purchasers.